Designing of Samosir Ulos Weaving Craft Center by Metaphorical Architecture - Imam Faisal Pane; Rofi Bintang Mishael (Talenta Publisher, 2019)
Ulos weaving craft is one of the most famous cultures of the Batak tribe. And the Lumban Suhi-Suhi Toruan Village in Samosir District is one of the traditional villages that still maintain customs and native Batak Toba village. The residents of Lumban Suhi-Suhi Toruan village especially the women working as Ulos weavers, and Ulos from Lumban Suhi-Suhi Toruan village, have been quite well-known to foreign countries, however, at present, the number of weavers has diminished, and many types of Ulos cloth have become extinct because of losing its craftsman. The Samosir Ulos Weaving Craft Center is present as a tool that can maintain the Ulos handicrafts of the local community and also empower the community as a place to produce various types of Ulos. The research methodology starts by collecting data, literature studies, Surveys to research locations and also design problem-solving. From the research process by the existing one, this building use metaphor architecture theme as its concept. The choosing of the metaphor theme in the building is considered to be able to describe the function and also introduce the culture of Ulos to the community. The Bintang Maratur Ulos pattern and the Mangulosi ceremony is forming the metaphor concept of the building. With the research and design of the Ulos Samosir weaving center, this can be a consideration for the Samosir district government or local community leaders to make this facility.